Catabolite repression of the xyl operon in Bacillus megaterium. - Rygus, T (1992)
We characterized catabolite repression of the genes encoding xylose utilization in Bacillus megaterium. A transcriptional fusion of xylA encoding xylose isomerase to the spoVG-lacZ indicator gene on a plasmid with a temperature-sensitive origin of replication was constructed and efficiently used for single-copy replacement cloning in the B. megaterium chromosome starting from a single transformant. In the resulting strain, beta-galactosidase expression is 150-fold inducible by xylose and 14-fold repressed by glucose, showing that both regulatory effects occur at the level of transcription. Insertion of a kanamycin resistance gene into xylR encoding the xylose-dependent repressor leads to the loss of xylose-dependent regulation and to a small drop in the efficiency of glucose repression to eightfold. Deletion of 184 bp from the 5' part of the xylA reading frame reduces glucose repression to only twofold. A potential glucose-responsive element in this region is discussed on the basis of sequence similarities to other glucose-repressed genes in Bacillus subtilis. The sequence including the glucose-responsive element is also necessary for repression exerted by the carbon sources fructose and mannitol. Their efficiencies of repression correlate to the growth rate of B. megaterium, as is typical for catabolite repression. Glycerol, ribose, and arabinose exert only a basal twofold repression of the xyl operon, which is independent of the presence of the cis-active glucose-responsive element within the xylA reading frame.